Associations between observed and reported infant negative affectivity, fear and self‐regulation, and early communicative development—Evidence from the FinnBrain Birth Cohort Study. (29th September 2022) - Ollas‐Skogster, Denise; Rautakoski, Pirkko; Bridgett, David; Kataja, Eeva‐Leena; Karlsson, Hasse; Karlsson, Linnea; Nolvi, Saara
Abstract: Self‐regulation and language are intertwined abilities, but the nature of their relations in early childhood when both skills are still emerging is insufficiently understood. Our knowledge of the relations between early negative affectivity and preverbal and verbal communicative development is still limited. Further, observed and reported temperament capture how aspects of temperament operate in different settings but are rarely used in parallel in studies examining early language. During the period of rapid development, longitudinal studies are needed to identify early risk factors for delayed communicative development. We studied relations between aspects of emerging self‐regulation and negative affectivity using both observations at 8 months and mother‐reports at 6 and 12 months, and communicative development measured by gesturing and vocabulary at 14 and vocabulary at 30 months in 183 children. Mother‐reported self‐regulation was related to a higher use of communicative gestures and observed self‐regulation by gaze aversion to poorer receptive and expressive vocabulary at 14 months, but neither was significantly associated with vocabulary at 30 months. We found little evidence for associations between negative affectivity and fear in infancy and communicative development. Our findings highlight different aspects of self‐regulation as both potential risk and protective factors for communicative development. Mixed results indicate a need for a more detailed examination of different strategies of self‐regulation in different conditions and developmental stages to yield a deeper understanding of the relations between self‐regulation in infancy and communicative development.